Symposium 2: Understanding emerging knowledge spillovers in small-group learning settings: The role of project-based learning, friendship and work-relations - Rienties, Bart; Bohle Carbonell, Katerina; Alcott, Peter; Willis, Tony (Proceedings of the International Conference on Networked Learning, 2012)
Learning in authentic projects is supposed to enhance graduates knowledge, skills and future employment. However, in programmes with a large number of students, implementing project-based learning and providing helpful guidance, extensive feedback, and support by teachers can be cumbersome. While peer assessment traditionally is used for grading or marking peers, there is a call for more formative (for learning) assessment and feedback using ICT which goes beyond marking and grading. This study took place in a post-graduate course on Event Operations management, whereby 69 primarily international students were divided into nine teams and worked together for a sustained period of fourteen weeks on a high-stake assignment, namely running a successful and profitable event. For ascertaining whether inter- and intra-team learning and knowledge spillovers occurred during the course, we employed a method developed within the field of Social Network Analyses (SNA). We measured prior friendship and work relations during the first week, while possible knowledge spillovers between learners and teams were assessed during week 14. In contrast to previous research on evolution of knowledge spillovers in small-group settings by Hernandez Nanclares et al. (2012), our results seem to indicate that knowledge spillovers across teams reduced over time. While all nine teams had substantial work and friendship relations outside their own team at the beginning of the module, over time all teams became more focussed on learning within teams. While pre-existing friendship ties are significantly correlated to the post- measurements of learning and work networks, pre-existing work ties are more strongly correlated with learning ties after fourteen weeks, as confirmed by multiple regression quadratic assignment procedures. Although further research is needed to confirm the underlying dynamics why teams and learners became more internally focussed, we hypothesise that the instructional design (i.e. focus on competition) and task-assignment may have a stronger impact on reducing knowledge spillovers between learners and teams.